Public Space as a Territorial Linkage. Theory and Application in a Marginal Urban Community of México. - Hidalgo-Rasmussen, Alfredo Henry (Revista de Estudios Andaluces, 2017)
This article is based on understanding public space as territorial linkage, establishes a method for its diagnosis and for the development of a territorial strategy that identifies intervention projects geared towards urban renewal in the urban community of Santa Margarita, in the city of Guadalajara, México. This research concludes that this method can be applied to understand the territorial and social condition of public spaces and propose them as centralities and axis of urban development planning.